The Danube Basin as a High-Tech Transport Corridor Between the West and the East - Vasyl Gorbachuk; Maksym Dunayevsky; Seit-Bekir Suleymanov; Viktor Godliuk; Dmytro Rybachok (Кібернетика та комп'ютерні технології)
The study is devoted to the consideration of high-tech achievements and implementation of sustainable transport technologies in the Danube River basin. The benefits and importance of inland waterways for global logistics are analysed, emphasising the importance of integrated waterway networks for modern technologies, products and services. The economic and logistical aspects of international cooperation in the Danube basin are considered. It is demonstrated that the median value of LPI (logistics performance index) for landlocked countries is higher than for coastal countries (3.3 vs. 3.2, respectively), which is explained by the reliability of land routes and the availability of indirect access to the sea through effective international cooperation. The role of international organisations, such as the Danube Commission, in improving transport links in the region is highlighted. The introduction of sustainable transport technologies in inland shipping is discussed, which is key to the integration of the transport system into domestic logistics chains. In particular, the importance of improving the quality of transport services, including tracking, flexibility and reliability, is emphasised. Examples of cooperation between the Odesa National Maritime University and the Cybersecurity Centre of Ukraine in developing modern approaches to water transport management are given. The contribution of other universities and research institutions to the study of transport technologies and characteristics of transport networks is investigated. In addition to technological issues, the problems of international competition and information asymmetry, which are typical for transport corridors in the Black Sea region, are considered. Thus, the article emphasises the importance of integrating modern technologies into transport systems and international cooperation for the development of efficient and environmentally friendly logistics in the Danube basin.